Profile of selected woven textile wholesalers and retailers in Divisoria - Avisado, Ethel C.; Elumba, Patricia Santos (2003.)
This study is about the sourcing and selling practices and activities of selected Divisoria textile traders. Specifically, this study aimed to identify the practices Divisoria textile traders use to source the fabrics that they sell and the methods that they use to sell the fabrics, wholesale to manufacturers and other stores; and retail to walk-in customers. This study helps Clothing Technology majors and garment industry practitioners understand Divisoria textile market and its system of trade. This is important because Divisoria is the biggest marketplace for textiles in Metro Mnaila, and it has many unique characteristics that have not been widely documented. The sourcing practices identified according to the wholesalers and retailers in the study were practices 1) In choosing fabrics, 2) Determining amount of fabric to order, 3) Time frame for stocks to last, 4) Time frame for ordering and 5) Mechanics in ordering. Whether getting their fabrics from a local or imported source or a distributor, the main criteria by which the stores in the study choose fabrics that they stock is the capacity of the fabric to be marketable. The amount of fabric ordered is dictated by how long the trader expects or wants the stock to last. These are both affected by sales trends. The allowance time given for orders range from hours, which is the amount of time needed for local suppliers or distributors to deliver orders, to more than one month which is common for those who are involved in retailing, specifically, of special fabrics. The stores who participated in the study that also mostly import place their orders together to cut costs on shipping and handling. On the other hand, wholesalers who have local sources can just order fabrics according to the orders that they also get. A mixture of wholesale and retail stores do both, ordering together and individually, depending on the need. There are two ways of selling seen in Divisoria, these are wholesaling and retailing. In both, the highest consideration that the selected wholesalers and retailers who participated in this study, is low pricing. In selling, it was seen in the study that the selected Divisoria stores, working on the system of negotiable pricing is able to adjust its operations to address the needs of its consumer. There are some selling practices and techniques that are unique to this area. The stores that participated in this study are able to provide negotiable pricing to their customers as well as other perks like volume discounts, terms, delivery or even payment through cheques. These are no usually found in other textile stores. A preferred customer or suki relationship is also seen in the Divisoria stores in the study, especially in wholesale stores. For customers that are just walking-in and cannot avail of the practices allowed for favored customers or suki, negotiable pricing is still an option with pricing being allowed to be driven low. Low price is the highest competitive edge that Divisoria textile traders have. Prices in the stores that participated in the study have around at least Php 15.00 cost difference per yard of fabric as compared to fabric stores in malls and textile sections of department stores. Other retail attributes are given attention but only depending on the prerogative of the stall owners.
Thesis (BS Clothing Technology)--University of the Philippines Diliman
Keywords: Clothing trade -- Philippines; Vendors and purchasers -- Philippines -- Manila, Divisoria